2019
DOI: 10.1016/j.jjcc.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism, underlying substrate and predictors of atrial tachycardia following atrial fibrillation ablation using the second-generation cryoballoon

Abstract: Background: Data regarding atrial tachycardia (AT) following second-generation cryoballoon ablation (CBA) of atrial fibrillation (AF) are limited. Aim: To describe the incidence, mechanisms, and clinical predictors of ATs following CBA. Methods and results: In this retrospective single-center study 238 patients undergoing CBA for treatment of paroxysmal (91/238; 38.2%) or persistent AF were analyzed. During a mean follow-up of 11.9 AE 5.5 months recurrence of AF occurred in 49/238 patients (20.6%) and AT in 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
1
23
1
Order By: Relevance
“…The occurrence of atrial tachycardias after stand‐alone PVI without substrate modification is a known but less frequent finding during reablation, with incidences between 2.8% and 11.3% 5,6,19‐21 . Several small studies comparing ATs after stand‐alone RFC or CB PVI have been conducted, and the results are very heterogeneous 5,6,19‐23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of atrial tachycardias after stand‐alone PVI without substrate modification is a known but less frequent finding during reablation, with incidences between 2.8% and 11.3% 5,6,19‐21 . Several small studies comparing ATs after stand‐alone RFC or CB PVI have been conducted, and the results are very heterogeneous 5,6,19‐23 .…”
Section: Discussionmentioning
confidence: 99%
“…Different gap patterns have been described after index PVI with RFC versus CB 3,4 . A less‐common but clinically relevant finding is the occurrence of atrial tachycardia (AT) after stand‐alone PVI without prior substrate modification 5,6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately, half of these ATs arise from the LA, with most of the remainder involving the cavotricuspid isthmus . A more recent study reported a higher incidence of organized AT after cryoballoon ablation for paroxysmal and persistent AF, and these tended to occur in patients who had low voltage areas in the LA suggesting an underlying fibrotic process …”
Section: Underlying Substrate For Left Atrial Tachycardiasmentioning
confidence: 99%
“…7,8 A more recent study reported a higher incidence of organized AT after cryoballoon ablation for paroxysmal and persistent AF, and these tended to occur in patients who had low voltage areas in the LA suggesting an underlying fibrotic process. 9 Macroreentry is the mechanism of most ATs after pulmonary vein isolation (about 60%-70%), whereas the remainder are classified as focal mechanisms. 10,11 When more extensive substrate ablation is performed for AF, ATs are more likely to occur.…”
Section: Underlying Substrate For Left Atrial Tachycardiasmentioning
confidence: 99%